Effects of zinc on the production of alcohol by Clostridium carboxidivorans P7 using model syngas. (1st January 2018) - Li, Demao; Meng, Chunxiao; Wu, Guanxun; Xie, Bintao; Han, Yifan; Guo, Yaqiong; Song, Chunhui; Gao, Zhengquan; Huang, Zhiyong
Abstract: Renewable energy, including biofuels such as ethanol and butanol from syngas bioconversed by Clostridium carboxidivorans P7, has been drawing extensive attention due to the fossil energy depletion and global eco-environmental issues. Effects of zinc on the growth and metabolites of C. carboxidivorans P7 were investigated with model syngas as the carbon source. The cell concentration was doubled, the ethanol content increased 3.02-fold and the butanol content increased 7.60-fold, the hexanol content increased 44.00-fold in the medium with 280 μM Zn 2+, when comparing with those in the control medium [Zn 2+, (7 μM)]. Studies of the genes expression involved in the carbon fixation as well as acid and alcohol production in the medium with 280 μM Zn 2+ indicated that fdhII was up-regulated on the second day, acs A, fdhII, bdh35 and bdh50 were up-regulated on the third day and bdh35, acsB, fdhI, fdhIII, fdhIV, buk, bdh10, bdh35, bdh40 and bdh50 were up-regulated on the fourth day. The results indicated that the increased Zn 2+ content increased the alcohol production through increase in the gene expression of the carbon fixation and alcohol dehydrogenase.